2008
DOI: 10.1016/j.vetmic.2008.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological survey of swine influenza A virus in selected wild boar populations in Germany

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 17 publications
2
23
0
2
Order By: Relevance
“…Influenza infections in wild boars were reported in the United States (Gipson et al, 1999;Corn et al, 2009), France (Vittecoq et al, 2012), Germany (Polley et al, 2007;Kaden et al, 2008), Poland (Markowska-Daniel and Pejsak, 1999Markowska-Daniel and Kowalczyk, 2005), and Spain (Vicente et al, 2002;Closa-Sebastia et al, 2011). Our survey is consistent with previous investigations showing that coinfection of H1 and H3 influenza viruses is common in feral swine.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Influenza infections in wild boars were reported in the United States (Gipson et al, 1999;Corn et al, 2009), France (Vittecoq et al, 2012), Germany (Polley et al, 2007;Kaden et al, 2008), Poland (Markowska-Daniel and Pejsak, 1999Markowska-Daniel and Kowalczyk, 2005), and Spain (Vicente et al, 2002;Closa-Sebastia et al, 2011). Our survey is consistent with previous investigations showing that coinfection of H1 and H3 influenza viruses is common in feral swine.…”
Section: Discussionsupporting
confidence: 91%
“…Only a few investigators have examined exposure of feral swine to influenza viruses (Kaden et al, 2008;Closa-Sebastia et al, 2011;Vittecoq et al, 2012). Direct detection of viral antigen in feral swine is difficult because of the short course of the infection.…”
Section: Introductionmentioning
confidence: 99%
“…The H1N1 subtype seems to be the most prevalent one among wild boars [39]. H3N2 influenza viruses were yet isolated too from naturally infected wild boars in Germany [40]. The sources of that wild boar infectedness could be pigs, humans or birds.…”
Section: Presumed Natural History Of Pandemic Influenza Strainsmentioning
confidence: 99%
“…Although many studies have examined influenza virus ecology in domestic pigs, the level of SIV circulation in the wild boar ( Sus scrofa ) population is unclear, as few studies have examined SIV infection in these animals [4, 5, 10, 15, 19, 22,23,24]. In particular, the prevalence of A (H1N1) pdm09 infection in wild boars is unclear, because no surveillance studies have been performed.…”
mentioning
confidence: 99%
“…Recent studies performed in Finland, Slovenia and France did not identify any wild boar that was seropositive for SIV [5, 10, 24]. However, another study found that 45% and 74% of wild boars in China were seropositive for subtypes H1 and H3, respectively [15].…”
mentioning
confidence: 99%